Organization of PhD studies at the Faculty of Public Health of the Slovak Medical University in the context of practice - Horváthová, Eva; Tihányi, Juraj (Central European journal of public health, 2024)
OBJECTIVES: The Slovak Medical University (SMU) holds a unique position in the health education system in Slovakia. It has a direct connection to the health sector, allowing health education to reflect the actual needs in this field. Because of increasing importance of public health in the last decades, more attention must be given to disease prevention and the promotion of healthy lifestyles. We aim to highlight the main characteristics of health higher education at one of the specialized health universities in Slovakia, with a particular focus on public health and its practical impacts. METHODS: We analysed the available legal regulations for postgraduate studies in Slovakia and the officially valid documents of the Faculty of Public Health (FPH) and the Slovak Medical University in accordance with the accredited study programme in Public Health. Archived data from the Department of Science, Research, and Doctoral Studies of the Faculty over the past 10 years were used for the analysis of postgraduate studies (2013-2023). RESULTS: PhD studies in Slovakia are conducted in accordance with Act No. 131/2002 Coll. on Higher Education Institutions and on amendments to certain acts. There are two forms of PhD study in Slovakia: full-time and external. The evaluation of study results is based on the credit system. The doctoral study programme proceeds according to an individual study plan under the guidance of the advisor. The PhD study concludes with the defence of the dissertation, which serves as the final thesis. A total of 97 students have graduated at FPH SMU in Public Health in the last 10 years. The majority of graduates were females (68% vs. 32% males) and studied in the external form of study (80.4% vs. 19.6% in the full-time programme). The most frequent research topics at FPH SMU in the last 10 years included Epidemiology and Prevention of Non-communicable (21.7%) and Infectious Diseases (11.3%), Health Management and Policy (17.5%), Environmental Health (15.5%), as well as Occupational Health (13.4%). CONCLUSION: High-quality and innovative postgraduate education in public health plays a crucial role in this field, preparing experts for the public health services. From a quality perspective, it is substantial to share experiences with various study programmes across the European region, as well as with other universities. Graduates of the Faculty of Public Health are highly sought-after professionals with diverse career opportunities not only in Slovakia but also within the European Union, other countries, and various important international institutions.
Keywords: veřejné zdravotnictví; Female; health promotion; ženské pohlaví; PhD studies; Slovakia; lidé; Schools, Public Health; public health; Public Health; studium vysokoškolské; Male; Education, Graduate; akademický sbor lékařské fakulty; postgraduate education; Universities; Slovenská republika; Faculty, Medical; mužské pohlaví; univerzity; školy veřejného zdravotnictví; Humans